CUNANG FISH FILLETS (Muraenesox Cinerus) WITH THE APPLICATION OF GMP AND SSOP - Pola Sabar Tumohon Panjaitan; Indri yanni; Riza Rizkiah; Liliek Soeprijadi (Universitas Mataram, 2024)
Cuckang fish (Muraenesox cinerus) are widespread in Indonesian waters, have an elongated body shape like an eel. The name of the cuckang fish (Muraensox cinerus) is different in each region, in the Pati area this fish is called